Immune checkpoint inhibitor-induced hypophysitis: lessons learnt from a large cancer cohort. (29th December 2021) - Kotwal, Anupam; Rouleau, Samuel G; Dasari, Surendra; Kottschade, Lisa; Ryder, Mabel; Kudva, Yogish C; Markovic, Svetomir; Erickson, Dana
Abstract : Immune checkpoint inhibitors (ICIs) can cause pituitary dysfunction due to hypophysitis. We aimed to characterize ICI-induced hypophysitis and examine its association with overall survival in this single-center retrospective cohort study of adult patients with cancer who received an ICI from January 1, 2012 through December 31, 2016. A total of 896 patients were identified who received ipilimumab alone (n=120); ipilimumab and nivolumab (n=50); ipilimumab before or after pembrolizumab (n=70); pembrolizumab alone (n=406); and nivolumab alone (n=250). Twenty-six patients (2.9%) developed hypophysitis after a median of 2.3 months. Median age at the start of ICI was 57.9 years and 54% were men. Hypophysitis occurred in 7.9% of patients receiving ipilimumab alone or in combination or sequence with a programmed cell death protein 1 inhibitor; 1.7% after pembrolizumab alone, never after nivolumab alone. Secondary adrenal insufficiency occurred in all hypophysitis cases. Use of ipilimumab alone or in combination was associated with pituitary enlargement on imaging and mass effects more frequently than pembrolizumab alone. Occurrence of hypophysitis was associated with improved overall survival by univariate analysis (median 50.7 vs 16.5 months; p=0.015) but this association was not observed in multivariable landmark survival analysis (HR for mortality 0.75; 95% CI 0.38 to 1.30; p=0.34) after adjusting for age, sex and malignancy type. To conclude, hypophysitis occurred most frequently after ipilimumab and manifested as anterior hypopituitarism affecting the corticotrophs more commonly than thyrotrophs and gonadotrophs. Mass effects and pituitary enlargement occurred more frequently in ipilimumab-induced hypophysitis. The association of hypophysitis with overall survival needs further investigation.